Development of a Mental Health Classifier Using LSTM and Text Preprocessing Techniques - Haryoko, Priyo; Syukur, Abdul; Rijati, Nova (Universitas Negeri Semarang, 2025)
Purpose: This study aims to address undiagnosed mental health conditions using social media for early detection. By applying advanced preprocessing techniques and LSTM models, the research improves classification accuracy for depression and PTSD. It highlights deep learning’s potential to process unstructured data and provides a scalable solution for real-world mental health monitoring. Methods: Data was collected from Twitter using keywords like